2022
DOI: 10.1111/lam.13591
|View full text |Cite
|
Sign up to set email alerts
|

Tea crude extracts effectively inactivate severe acute respiratory syndrome coronavirus 2

Abstract: It is well known that black and green tea extracts, particularly polyphenols, have antimicrobial activity against various pathogenic microbes including viruses. However, there is limited data on the antiviral activity against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), which emerged rapidly in China in late 2019 and which has been responsible for coronavirus disease 2019 (COVID‐19) pandemic globally. In this study, 20 compounds and three extracts were obtained from black and green tea and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Tea drinking is commonly regarded as a convenient and safe complementary therapy and healthy habit. Recent modeling studies have shown that various tea components are highly effective in blocking SARS-CoV-2 infection ( 24 , 25 , 47 , 48 ). In addition, tea polyphenols might suppress the virus through their beneficial effects on intestinal microbiota ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tea drinking is commonly regarded as a convenient and safe complementary therapy and healthy habit. Recent modeling studies have shown that various tea components are highly effective in blocking SARS-CoV-2 infection ( 24 , 25 , 47 , 48 ). In addition, tea polyphenols might suppress the virus through their beneficial effects on intestinal microbiota ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the dramatic effect of green tea on dangerous viral diseases. 12 , 13 . Recent studies have shown that epigallocatechin-3-gallate (EGCG) in green tea has antiviral effects.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that this effect was not produced by just one compound, and that multiple components in tea work synergistically and in a concentration-dependent manner. The use of tea concentrate as an oral spray formulation may inactivate the virus in the mouth for preventive purposes [ 74 ].…”
Section: The Effects Of Tea On Covid-19 and Its Sequelaementioning
confidence: 99%